THE IMPLEMENTATION OF THE SCIENCE OF TAJWID IN LEARNING OF THE AL-QUR’AN WITH THE TAJWID WHEEL METHOD TO DEVELOP THE READING OF THE QUR’AN IN IBTIDAIYAH MADRASAH - Muhammad Syaifullah; Miftahul Jannah; Noveria Fradila; Putri Pramestia Nigrum; Susanti Santi; Wirdania Nasution (Universitas Trunojoyo Madura, 2022)
The purpose of the research is to be able to develop students' skills in reading the Qur'an in accordance with the practice of recitation science using the recitation wheel method. This type of research uses research and development or Research and Development (RD). Where this method conducts research and development which can also be interpreted as a scientific step that has the aim of researching, designing, producing or producing products and testing the validation of the products that researchers have presented. Research and development is also referred to as research, design, production, and testing. Based on the results obtained in the field, it shows that the use of the recitation wheel is able to make students better understand the science of recitation and can apply it when reading the Qur'an.